Effect of automated red cell exchanges on oxygen saturation on-air, blood parameters and length of hospitalization in sickle cell disease patients with acute chest syndrome - Aneke, John C. (Niger Med J, 2016)
BACKGROUND: Red cell exchanges (RCEs) lead to improvement in tissue oxygenation and reduction in inflammatory markers in sickle cell disease (SCD) patients who present with acute chest syndrome (ACS). The aim of this study is to evaluate the effects of automated-RCE (auto-RCE) on oxygen saturation (SpO(2)) on-air, blood counts, the time to correct the parameters and length of hospitalization after the exchange in SCD patients presenting with ACS. SUBJECTS AND METHODS: This was 2 years study involving five SCD patients; the time for SpO(2) on air to increase to ≥95% and chest symptoms to resolve, postprocedure, as well as the length of in-patient hospitalization was recorded. All data were entered into Statistical Package for Social Sciences Version 20.0 (SPSS Inc., Chicago, IL, USA) computer software for analyses. RESULTS: The study involved 4 (80%) hemoglobin (Hb) SS and 1 (20%) HbSC patients. The median time of SpO(2) recovery was 24 h, ranging from 6 to 96 h. About 60% (3/5) of patients achieved optimal SpO(2) within 24 h post-RCE, while discharge from intensive care unit was 24 h after auto-RCE in one patient. The Hb concentration was significantly higher, while the total white cell and absolute neutrophil counts were significantly lower at the time of resolution of symptoms, compared to before auto-RCE (P < 0.05). The average post auto-red cell transfusion symptoms duration was 105.6 (24–240) h while mean inpatient stay was 244.8 (144–456) h. CONCLUSION: Auto-RCE could reverse hypoxia in ACS within 24 h.